ANALYS OF THE FISCAL SPACE TRANSFORMATION OF UKRAINE - Kryhan, Yurii (Socio-economic relations in the digital society, 2020)
In the current conditions of globalization, financial crisis in the world, the negative impact of the COVID-19 pandemic on the development of states, the activities of all economic entities and interstate relations, economic instability in the state, it is necessary to allocate and use public funds and regulate fiscal space. National economies and their constituent systems are interconnected by fiscal relations, which are subject to transformation and influence due to constant changes in external and internal factors: economic crises, currency fluctuations, political imbalances between countries, military conflicts, natural disasters, etc. To develop the country’s economy and increase its financial security, it is necessary to effectively regulate budget processes: their revenues and expenditures, so there is a need to analyze the transformation of the fiscal space of Ukraine. The main purpose of the study is to analyze the transformation of the fiscal space of Ukraine in modern conditions. The analysis of transformation of fiscal space of Ukraine is carried out. The definition of the concept of fiscal space is indicated. The main properties of fiscal space are considered and the sources of its creation are schematically presented. Revenues of the consolidated budget of Ukraine are analyzed. The level of implementation of the planned indicators of budget revenues and expenditures is determined. The average shares of revenues of the consolidated budget of Ukraine during the study period are calculated. The generalized (average) structure of revenues of the consolidated budget of Ukraine is presented. The structure of actually received revenues of the consolidated budget of Ukraine is investigated. The dynamics of received and planned total revenues of the consolidated budget of Ukraine is graphically presented. The main source of fullness of the revenue part of the budget of Ukraine is revealed. The dynamics of tax revenues to the state, local and consolidated budgets is analyzed and their structures are considered. Expenditures of the consolidated budget of Ukraine are investigated. The dynamics and structure of expenditures according to the program classification of expenditures and crediting of the state budget, according to the economic classification of budget expenditures and according to the functional classification of expenditures and crediting of the budget are analyzed. We are convinced that the analysis of the transformation of Ukraine’s fiscal space will improve the mechanisms of regulating budget processes and attracting insufficient funds, which will increase the financial security of the state and the economy, reduce public debt and creditors, develop interstate relations and more.